Towards promotion of local tourism : a case study of the Kenya Wildlife Service outreach program - Kassilly, Fredrick Nyongesa (Array, 2008)
Summary: In an effort to promote local tourism, Kenya Wildlife Service (KWS) launched a cost-sharing outreach program in Nakuru Municipality involving a free bus to take residents for wildlife viewing tours in Lake Nakuru National Park (LNNP) during weekends and national holidays upon payment of park entrance fees. I joined in the tours between September and December 2006 and using a questionnaire personally interviewed 256 of the residents to evaluate the program's impact on their relations with KWS and the management of LNNP, how it stimulated the need for recreational wildlife viewing among them, and identify the program's weaknesses and the residents' views for its improvement. Results reveal high potential for sustainable local tourism among residents of Nakuru Municipality. Popular opinion was that the program had improved residents' relations with KWS and with the management of Lake Nakuru National Park, had made them appreciate recreational and aesthetic values of wildlife and generated demand for wildlife viewing as a pastime. Respondents were unanimous that one bus was not enough for the program and a majority felt the game drives were too short although they were set for a repeat visit to the park. Most respondents visited the park with companions comprising friends and family members. The program was rated a success and improvements are proposed for better satisfaction of residents. Where feasible the Lake Nakuru National Park example should be extended to other wildlife protected areas to boost local tourism and improve relations between wildlife managers and local communities in Kenya